Kesenjangan Pembangunan Ekonomi Antar Provinsi di Kawasan Indonesia Timur - Fivit Baktirani; Darwis Amin (TAHKIM, 2018)
This study aims to determine the level of economic and development inequality in provinces in Eastern Indonesia and to determine the level of income inequality between regions/provinces in Eastern Indonesia. This type of research is library research with analysis tools using the Williamson index and Klassen Typology. The type of data used in this study is secondary data which is based on GRDP data and the rate of economic growth in the provinces of Eastern Indonesia. The research results show that 1). quadrant I with a high economic growth rate followed by a high GRDP growth rate is also dominated by Papua Province, South Sulawesi Province, Central Sulawesi Province; Quadrant II, namely the low economic growth rate but the high GRDP growth rate is dominated by West Nusa Tenggara Province. In the third quadrant, where the economic growth is high but the per capita income is low, it is dominated by North Maluku Province, West Sulawesi Province and Southeast Sulawesi Province. In the fourth quadrant, which are regions with low economic growth and low per capita income, are dominated by Gorontalo Province, Maluku Province, East Nusa Tenggara Province, West Papua Province and North Sulawesi Province. 2. Income inequality in the Eastern Indonesia region from 2010 to 2021 is relatively moderate, namely an average of 0.44 which indicates that most regions have a high level of economic growth and per capita income above the provincial average in the Eastern Indonesia region.Keyword: Gap, Income, Klassen Typology, Williamson Index.